Intraluminal duodenal (“windsock”) diverticulum: a rare cause of biliary obstruction and acute pancreatitis in the adult - Karagyozov, Petko; Tishkov, Ivan; Georgieva, Zhenya; Boeva, Irina; Tzankov, Dimitar (Endoscopy International Open, 2019)
An intraluminal duodenal diverticulum (IDD) is a rare congenital anomaly, which is a result of incomplete recanalization of the foregut lumen during embryonic development. Most patients are asymptomatic. Symptoms usually occur after the third decade of life and mainly include epigastric pain, nausea, vomiting, or bloating. Less commonly, IDD may complicate with bleeding, duodenal obstruction, or acute pancreatitis. We present a case of IDD, manifested for a first time in adult with acute biliary obstruction and mild pancreatitis after laparoscopic cholecystectomy for acute calculous cholecystitis, successfully managed with endoscopic retrograde cholangiopancreatography (ERCP).